A numerical study on mechanisms of energy dissipation in a pump as turbine (PAT) using entropy generation theory. (December 2020) - Ghorani, Mohammad Mahdi; Sotoude Haghighi, Mohammad Hadi; Maleki, Ali; Riasi, Alireza
Abstract: The utilization of pumps in reverse function is one of the economically beneficial methods for off-grid power generation in micro-hydropower capacities. The traditional method of hydraulic loss calculation in turbomachinery based on pressure drop calculations is unable to determine the exact location of losses. In this paper, the irreversible energy losses within the PAT has been studied for the first time using entropy generation theory and the second law of thermodynamics point of view. In order to conduct numerical simulation, the 3-dimensional incompressible steady-state flow within the PAT is simulated by solving the Reynolds averaged Navier-Stokes (RANS) equations. The shear stress transport (SST) turbulence model is considered for turbulence modeling. The quantity of direct (viscous) and turbulent entropy generation rate is calculated in different PAT components in 9 different flow rates in the range of 0.7QBEP to 1.3QBEP . The numerical results show that the turbulent term is the main factor of entropy production within the PAT (86.89%–90.98%), and thus, turbulent entropy generation is the dominant mechanism for hydraulic losses. More than 50% of the energy dissipation occurs within the PAT runner. Most of the losses within the runner take place at the blade leading edge, blade trailing edge and flow separation regions of the blade suction and pressure sides. The volumetric entropy generation rate analysis demonstrates that the draft tube has the most potential to generate irreversible losses among all the components (47.37%). Flow field analysis reveals that the blade inlet shock, flow deviation at the blade outlet, flow separation, backflow and vortices in flow passages are categorized as the main reasons for entropy production and irreversible hydraulic losses within the PAT components. The advantages of the entropy generation method including the determination of the exact location and quantity of energy dissipation within the PAT are indicated in this investigation. Highlights: The irreversible energy losses within the PAT has been studied. Most of the losses within the runner take place at the blade leading edge and blade trailing edge. Draft tube has the most potential to generate irreversible losses among all the components (47.37%). Blade inlet shock, flow deviation, flow separation are categorized as the main reasons for entropy production.